Pengaruh Mobilitas Penduduk dan Indikator Sosial Ekonomi terhadap Emisi Karbon di Indonesia Tahun 2020–2022: indonesia - Kurniasari, Agustin; Sakina, Dara; Zaldi, Muhammad Afif Wirdiyan; Kurniawan, Robert (Teknik Lingkungan Universitas Islam Indonesia, 2026)
Indonesia is one of the world's largest contributors to carbon emissions, primarily from the fossil-fueled land transportation sector. The COVID-19 pandemic demonstrated that a reduction in mobility could significantly decrease emissions, especially in densely populated areas with suboptimal public transportation systems. In addition, inequality in population distribution and differences in socioeconomic characteristics between regions lead to environmental pressures that vary across Indonesia. This study aims to analyze the impact of population mobility and socio-economic indicators on carbon monoxide (CO) emissions in Indonesia during the unique pandemic period of 2020-2022. The method used is the Random Effect Model for panel data regression. The results show that mobility to workplaces and stores, economic growth, and poverty levels have a significant negative effect on emissions. Conversely, mobility in residential areas and population density have a significant positive effect. The variables of mobility to transit stations and Foreign Direct Investment (FDI) were found to be not significant. These findings point to the need for low-emission transportation and household energy efficiency policies that are responsive to mobility dynamics and socio-economic characteristics of the community.